2021
DOI: 10.1038/s41598-021-00337-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with chronic disease: results from the population-based Lifelines Cohort Study

Abstract: Abstract(1) To evaluate the prevalence of severe and chronic fatigue in subjects with and without chronic disease; (2) to assess to which extent multi-morbidity contributes to severe and chronic fatigue; and (3) to identify predisposing and associated factors for severe and chronic fatigue and whether these are disease-specific, trans-diagnostic, or generic. The Dutch Lifelines cohort was used, including 78,363 subjects with (n = 31,039, 53 ± 12 years, 33% male) and without (n = 47,324, 48 ± 12 years, 46% male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 58 publications
5
44
0
3
Order By: Relevance
“…Our findings that high anesthetic risk score influences LOS is consistent with previous work [ 62 ]. Fatigue is a complex phenomenon, experienced by people with a wide range of chronic diseases and it incorporates disease-specific and psychosocial factors [ 63 ]. It is more highly correlated with the number of chronic diseases experienced rather than the severity of chronic disease [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings that high anesthetic risk score influences LOS is consistent with previous work [ 62 ]. Fatigue is a complex phenomenon, experienced by people with a wide range of chronic diseases and it incorporates disease-specific and psychosocial factors [ 63 ]. It is more highly correlated with the number of chronic diseases experienced rather than the severity of chronic disease [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a complex phenomenon, experienced by people with a wide range of chronic diseases and it incorporates disease-specific and psychosocial factors [ 63 ]. It is more highly correlated with the number of chronic diseases experienced rather than the severity of chronic disease [ 63 , 64 ]. The majority of our TKA cohort evidenced multimorbidity, yet few studies have explored fatigue in the TKA population, despite relatively high prevalence in people with osteoarthritis [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate studies in brain tumor patients that found no link between fatigue and tumor location, disease duration, type of neurosurgical intervention, and radiation [8][9][10] . Also in cancer survivors and patients with chronic disease, the persistence of fatigue is not determined by tumor-and treatment-related characteristics 11,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Dutch population-based study demonstrated that the prevalence of fatigue is similar across several chronic diseases, and is associated with factors such as depression, female sex, younger age, lower education level, neuroticism, self-consciousness, impulsivity, vulnerability, and pain 11 . We also found several PROMs to be associated with fatigue, unlike tumor-and treatment-related factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation